Homogenisasi Sekunder terhadap Kadar Hemoglobin - Rosnita Sebayang; Hotman Sinaga; Mustika Sari Hutabarat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the results of hemoglobin examination with secondary homogenization techniques 3, 5, 7, and 8 times, after being left for 60 minutes after primary homogenization. The research method used is pre-experimental research. The results showed that the average hemoglobin measured by an automatic hematology analyzer in the secondary homogenized blood group was 3 times 13.3 g/dl, homogenized 5 times 13.1 g/dl, homogenized 7 times 13.2 g/dl, and homogenization 8 times 13.1g/dl. In conclusion, there is no difference in hemoglobin levels in the secondary homogenization process 3, 5, 7, and 8 times. Keywords: EDTA Blood, Hemoglobin, Homogenization